STUDENTS’ RESPONSE TO THE IMPLEMENTATION OF TEAMS GAMES AND TOURNAMENT(TGT)-BASED OUTDOOR STUDY AT MTsN 3 PACITAN - Fauziah Hanin (Pendidikan IPA, FMIPA, UNP, 2020)
The objective of this paper is to determine students’ response to the implementation of Teams Games and Tournament (TGT)-based outdoor study in natural science subject. Data were collected by questionnaire and interview, then tabulated in Microsoft Excel and analyzed descriptively. Results of the study showed that the average of the questionnaire were 3,86. These results indicate that the students’response were very good. Teams Games and Tournament (TGT) based on outdoor study made students more happy, motivated, skilled, and active to participate in learning, because they could play and saw real examples of the material being studied.